2015
DOI: 10.2319/111914-830.1
|View full text |Cite
|
Sign up to set email alerts
|

Vibratory stimulation increases interleukin-1 beta secretion during orthodontic tooth movement

Abstract: Objectives: To investigate the effects of application of vibratory stimuli on interleukin (IL)-1b secretion during maxillary canine distalization. Materials and Methods: Split-mouth design study in 15 subjects (mean age, 22.9 years; range 19-25 years) whose bilateral maxillary first premolars were extracted with subsequent canine distalization. On the experimental side, light force (60 g) was applied to the canine for 3 months in combination with vibratory stimuli provided using an electric toothbrush 15 minut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
94
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(113 citation statements)
references
References 20 publications
6
94
2
2
Order By: Relevance
“…In agreement with these findings Leethanakul et al found higher concentration of IL-1β in canines after electric toothbrush application for 2 months (16). Interestingly, in their study a higher rate of maxillary canine distalization was also reported.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…In agreement with these findings Leethanakul et al found higher concentration of IL-1β in canines after electric toothbrush application for 2 months (16). Interestingly, in their study a higher rate of maxillary canine distalization was also reported.…”
Section: Discussionsupporting
confidence: 77%
“…Contrary to these findings, Pavlin et al (19) reported that low-level cycling loading of 0.25N at 30 Hz released by the same vibrational appliance used in the study of Miles et al increases the rate of orthodontic tooth movement (OTM) when applied as adjunct to orthodontic treatment. In a recent study Leethankul et al investigated through a split-mouth study the levels of IL-1β in gingival cervicular fluid and the rate of orthodontic tooth movement in canines stimulated by electric toothbrush compared to standard orthodontic movement of canines (16). They found enhanced secretion of IL-1β and accelerated OTM in canines stimulated by electric toothbrush vibrations.…”
Section: Ivyspring International Publishermentioning
confidence: 99%
See 1 more Smart Citation
“…21 The GCF absorbed on each paper point was diluted with 250 lL of sterile phosphate-buffered saline (pH 7.4), centrifuged (13,000 g at 48C for 15 minutes), and stored at À808C until analysis. 22 The Periotron was always calibrated before GCF sampling. 21 …”
Section: Cgf Samplingmentioning
confidence: 99%
“…The vibration tests were carried out for 5 minutes, and the resonance curves were displayed as frequency-force relationships on the monitor of the vibration controller. Clinical trials were conducted by various researchers [43][44][45][46][47] on human population using oral vibrating devices such as AccledentTM, AcceleDent® and electric tooth brushes and found to be effective in increasing the rate of tooth movement. Two cross sectional animal studies [43,44] done on cyclic vibration.…”
Section: Cyclic Vibrationsmentioning
confidence: 99%